Short Run and Long Run Associationship between Real Exchange Rate and Trade Balance: Empirical Evidence from Bangladesh (Johansen Approach and Vector Error Correction Model) (Global Journal of Human-Social Science, 2019)
Several studies have tested the j curve phenomenon for Australia, Japan, South Korea, New Zealand and many other countries using non stationary time series data and have provided mixed results. They not only suffer from the aggregation bias problem but also the spurious regression problem. To overcome this problem, in this paper we investigate the short run and long-run effects of real depreciation of the Bangladeshi taka to the trade balance between Bangladesh and her trading partners. In this article first we check the stationary of data set and find the stationary applying the Augmented Dickey Fuller test, then applying the Johansen co integration test in order to find out the long run co integrated equations and last of all try to investigate the short run and long run relationship among the variables, while we use the VECM (vector error correction model) and found that there is long run associations among the variables, and short-run coefficients are statistically insignificant. But for Bangladesh j curve concept have not been tested yet. That's why we have chosen this topic, and we incorporated several others variables to test the linkages on trade balance such as GNI as a proxy of GDP, inflation rate, NODA (net officials development assistance, and we have given more priory on the variable real exchange rate.